Control of anisotropy of a redox-active molecule-based film leads to non-volatile resistive switching memory. Issue 47 (21st October 2019) - Kim, Jaejun; Ohtsu, Hiroyoshi; Den, Taizen; Deekamwong, Krittanun; Muneta, Iriya; Kawano, Masaki
Abstract : Control of the π–π interaction direction in a redox-active π-molecule based film led to the formation of new mechanistic non-volatile resistive switching memory. Abstract : Control of the π–π interaction direction in a redox-active π-molecule based film led to the formation of new mechanistic nonvolatile resistive switching memory: a redox-active organic molecule, 2, 5, 8-tri(4-pyridyl)1, 3-diazaphenalene, showed non-volatile bistable resistance states with a high on-off ratio, retention, and endurance only when the molecular orientation was anisotropic. Control experiments using redox-active/redox-inert organic molecules with isotropic/anisotropic molecular orientations implied that the formation of conductive oxidized π–π stacking layers from non-conductive neutral π–π stacking layers is responsible for resistive switching phenomena, indicating new mechanisms such as ReRAM. Our findings will give a comprehensive understanding of electron transport in organic solid materials based on the effects of redox-activity and molecular arrangement, leading to fabrication of a new class of ReRAM based on organic molecules.